THE ROLE OF NON-FERROUS METALS IN THE DEVELOPMENT OF ELECTRICAL ENGINEERING (Archive of Conferences, 2020)
The role of non-ferrous metals in the development of electrical and radio engineering and the role of non-ferrous metals in the transmission of electricity